Pemberdayaan Anak Yatim LAZNAS PPPA Daarul Qur’an Lampung melalui Pendanaan Pendidikan Berbasis Filantropi Islam (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This research was conducted with the aim of analyzing and finding out about the empowerment of orphans at LAZNAS PPPA Daarul Qur'an Lampung through Islamic philanthropy-based educational funding. The approach used in this research is descriptive qualitative, using a case study method. The data collection process involved observation, interviews, and document review. Data analysis included data collection, data reduction, data presentation, and conclusion drawing, as well as data validation through triangulation. This study revealed that educational funding rooted in Islamic philanthropy at LAZNAS PPPA Daarul Qur'an Lampung includes budget revenues and expenditures with allocations prepared at the beginning of each year. The expenditure period can be tracked through the LAZNAS PPPA Daarul Qur'an Lampung online system. Distribution efforts include eliminating educational costs for orphans, providing basic necessities, distributing Mushabs for orphaned students who memorize the Qur'an, and supporting orphans. The evaluation of Islamic philanthropy-based education funding at LAZNAS PPPA Daarul Qur'an Lampung involved an analysis that showed that the role of the nadzir (manager) remains limited. All responsibilities and functions of the nadzir, particularly those of branch heads and fundraisers, are aimed at improving management. Furthermore, accountability is a factor taken into account when drafting the budget for the upcoming period.